Gambaran Pengaruh Terapi Beapreasi Terhadap Efikasi Diri Pada Individu Penyakit Kronis Di Puskesmas Bergas Kabupaten Semarang - Fiktina Vifri Ismiriyam; Wulansari Wulansari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Self-efficacy is the perception of the ability to consider and implement behavior patterns as self-regulation that is obtained through motivation and determining achievement of expectations. Good self-efficacy is needed not only for healthy people but also for sick people, especially people with chronic illnesses. Decreased self-efficacy can occur in people with chronic illnesses. We know that people with chronic diseases have long treatment programs, even for a lifetime, such as taking medication and sometimes this feels boring or boring. Consuming drugs or running a continuous treatment program can lead to boredom so that it is possible to want to stop taking medication. This is the background for wanting to know what actions can be taken to increase self-efficacy in people with chronic diseases. Self-efficacy increases if there is effort in dealing with existing obstacles. Interventions can be provided by health workers in increasing self-efficacy in people with chronic diseases. Objective: This study aims to describe the effect of Beapreasi therapy on self-efficacy in patients with chronic diseases at the Bergas Health Center, Semarang Regency. Methods: The research design used was descriptive and was carried out on 6 respondents, all of whom became the experimental group or all of whom became respondents. The method used to determine respondents is a purposive sampling technique. All respondents were assessed for self-efficacy using a self-efficacy scale questionnaire which was measured 2 times, namely before and after being given Beapreasi therapy. Results: The study showed that the mean value of the self-efficacy scale in the experimental group before the intervention was 81.79 and the value of the efficacy scale in the experimental group after the intervention was 89.36. this shows that there is an increase in the value on the self-efficacy scale and there is a difference in the mean value on the self-efficacy scale in the experimental group before giving the intervention with after giving the intervention with a p value of 0.00, p value <0.05 so that there is a significant/significant effect of giving reward therapy on improvement self-efficacy. Conclusion: Beapreasi therapeutic intervention can be used to maintain self-efficacy or increase self-efficacy in patients with chronic diseases, with the hope that patients will remain enthusiastic in carrying out their care and life. Beapreasi therapy can be used as a nurse's independent intervention in accompanying the care of patients with chronic diseases who require lifelong treatment and this is in an effort to increase self-efficacy in sufferers of chronic diseases.